Efficient hydrogen storage capacity of La3B18: A DFT study. (8th March 2023) - Sun, Xiyuan; Yin, Pengfei; Zhang, Yi; Zhang, Chuanyu; Feng, Xing; Jiang, Gang
Abstract: Boron-based nanomaterials are the potential mediums for hydrogen storage applications. In this work, we have employed density functional theory (DFT) calculations to assess the hydrogen storage performance of the high stable La3 B18 cluster (T. T. Chen et al., Nat. Commun, 2020, 11, 2766). Our results indicate that each La atom of the La3 B18 cluster can bind six H2 molecules at most, corresponding to a gravimetric density of 5.6%. The adsorption energy calculated with wB97XD functional are in the range of −0.126 to −0.179eV, which is in the desirable binding energy range. Interaction natures in the studied complexes were revealed by various electron density topological analyses. Ab initio molecular dynamics (AIMD) results show that the H2 molecules can be efficiently released. Our results predicted the La3 B18 cluster to be a promising hydrogen storage medium. Graphical abstract: Image 1 Highlights: La3 B18 cluster was investigated for hydrogen storage application. Each La atom attach six hydrogen molecules leading to 5.6 wt%. La3 B18 cluster adsorbs hydrogen molecules with the desirable binding energy. H2 molecules binding with La3 B18 cluster by coordination of Kubas and electrostatic interactions. H2 releases were investigated by molecular dynamics simulations.